Implementasi Media Tanaman Pisang Untuk Peningkatan Perkembangan Motorik Halus Anak Usia Dini - Ani Malisa; Dwi Nomi Pura; Syisva Nurwita (Early Childhood Research and Practice, 2026)
This study aims to determine whether the implementation of banana plant-based media—such as banana fruit, stems, and leaves—in the learning process can enhance the fine motor skill development of early childhood children aged 4–5 years. This study employed classroom action research. The subjects were 15 children from Group A at PAUD Cita Ananda, Kelindang Village. The results showed that: (1) teacher activity improved from a score of 50 (73.5%, categorized as "Good") in Cycle 1 to a score of 61 (89.7%, categorized as "Good") in Cycle 2; and (2) children's fine motor skill development improved, with the number of children in the "Developing Very Well" (BSB) category rising from 3 (20%) in Cycle 1 to 12 (80%) in Cycle 2, thereby meeting the success criterion of having 75%–100% of children in the BSB category. Implementing banana plant-based media in the teaching-learning process can enhance the fine motor skill development of children in Group A at PAUD Cita Ananda, Kelindang Village. Such media can be utilized in the teaching-learning process for children aged 4–5 years to improve their fine motor skills.